A Comparison of Machine versus Free-Weight Squats for the Enhancement of Lower-Body Power, Speed, and Change-of-Direction Ability during an Initial Training Phase of Recreationally-Active Women - Neil A. Schwarz; Sean P. Harper; Andy Waldhelm; Sarah K. McKinley-Barnard; Shelley L. Holden; John E. Kovaleski (MDPI AG, 2019)
The purpose of this study was to examine differences between a free-weight squat (FWS) and machine squat (MS) during an initial resistance training phase for augmentation of performance tests in recreationally active women. Twenty-seven women (22.7 ± 3.5 years) were block-randomized to three groups: FWS, MS, or control (CON) and completed pre- and post-testing sessions consisting of the squat one-repetition maximum (1-RM), vertical jump, pro-agility test, zig-zag change-of-direction (COD) test, and 30-meter sprint. Participants trained two sessions per week for six weeks by performing jumping, sprinting, and COD drills followed by FWS, MS, or no squats (CON). Peak jump power increased for CON (p = 0.03) and MS (p < 0.01) groups. Change in peak jump power was greater for the MS group compared with the FWS group (p = 0.05). Average jump power increased for the MS group (p < 0.01). Change in average jump power was greater for the MS group compared with the CON group (p = 0.04). Vertical jump height, pro-agility, 30-meter sprint, and zig-zag COD tests improved over time (p < 0.01), with no difference between groups (p > 0.05). Machine squat training maximized jumping power compared with FWS training and CON. Both resistance training groups and the CON group improved equally in the pro-agility, 30-meter sprint, and zig-zag COD tests. Machine squat training may provide performance-enhancing benefits of equal or superior value to those obtained with free-weight squat training in recreationally active women during an initial training mesocycle. These findings also stress the importance of task-specific training in this population of untrained women, as the control group improved in terms of performance to the same degree as both resistance training groups.